Proposal of Key Factors for User-Oriented Web Applications - Iveta Kremenova; Marian Galovic (Communications - Scientific letters of the University of Zilina, 2010)
The paper deals with issues regarding the identification of key-factors for a successful creation of a user-oriented web application. Described are methods of identification, sources of information and contents of each category. The categories are Search, Display, Home Page and Navigation. The categories are broken-down into a table form. The paper also presents the results of several web applications testing based on new identified key factors. The testing was performed by the Department of Communications using a sample of web pages.